2017
DOI: 10.5606/archrheumatol.2017.6070
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin B12, Homocysteine and Methylmalonic Acid Levels in Patients With Parenchymal Neuro-Behçet’s Syndrome

Abstract: Objectives: This study aims to investigate the role of serum levels of vitamin B12 (VitB12), homocysteine (Hcy), and methylmalonic acid (MMA) in the development of parenchymal neuro-Behçet's syndrome (NBS) and to compare them with healthy controls and Behçet's syndrome (BS) patients without NBS. Patients and methods: Serum VitB12, Hcy, and MMA were measured using enzyme-linked immunosorbent assay in 64 patients (36 males, 28 females; mean age 36±8.3 years; range 20 to 56 years) who met the criteria of the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The initial database search yielded 184 entries plus another 2 found on Google; following the screening and exclusion processes indicated in Fig. 1 , we identified 53 studies (52 full papers and one abstract) 6 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 examining the relationship between HC and BD (48 case–control and 5 cohort studies) that were included in our systematic review and meta-analysis ( Table 1 ). Of the 48 case–control studies, one did not report the mean ages of participants 22 and another did not report gender data (both full papers), 31 whereas a third (in abstract form only) did not report the mean ages and the gender data 40 : two missing data each for mean age of participants and for male/female ratio (4.1%) are unlikely to compromise the results of the sensitivity analysis; of the five cohort studies one did not report the mean age of participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial database search yielded 184 entries plus another 2 found on Google; following the screening and exclusion processes indicated in Fig. 1 , we identified 53 studies (52 full papers and one abstract) 6 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 examining the relationship between HC and BD (48 case–control and 5 cohort studies) that were included in our systematic review and meta-analysis ( Table 1 ). Of the 48 case–control studies, one did not report the mean ages of participants 22 and another did not report gender data (both full papers), 31 whereas a third (in abstract form only) did not report the mean ages and the gender data 40 : two missing data each for mean age of participants and for male/female ratio (4.1%) are unlikely to compromise the results of the sensitivity analysis; of the five cohort studies one did not report the mean age of participants.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty articles explored the relationship between HC and any vascular involvement; however, two studies were excluded at this stage: one dealt with venous incompetence only 58 and the other dealt with neuro-BD, with only five VTs in the latter group. 56 Hence, we pooled data from 18 studies comprising 927 BD participants without and 423 with vascular involvement: the effect size favored vascular involvement ( p < 0.0001) with wide heterogeneity ( I 2 = 89.7%, p < 0.0001) ( Fig. 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…We can see a clear positive correlation between BU and both arthralgia and parenchymal neurological involvement. On the other hand, there is an opposite association when it comes to genital ulcers, gastrointestinal symptoms, and other systemic symptoms [30][31][32][33]. These complex interactions highlight the need for further investigation to better understand the multifaceted pathogenesis of BD.…”
Section: Epidemiologymentioning
confidence: 99%
“…The MTHFR, catalyzing the synthesis of 5-methyltetrahydrofolate, is required for vitamin B12-dependent enzyme methionine synthase and Hcy regulation [ 24 , 25 ]. Vitamin B12 deficiency and Hcy imbalance have been identified to play a role in the pathology of psoriasis [ 26 ], MS [ 27 ], BD [ 28 ], AS [ 29 ], and GD [ 30 ]. Previously, some authors reported that the two genetic variants were risk factors for psoriasis [ 31 ], MS [ 32 ], and GD [ 33 ].…”
Section: Introductionsmentioning
confidence: 99%